Kamojing Dam Crisis Communications Model as an Effort to Mitigate Dam Failure Disaster - Muslimah, Tikka; Budhiharti, Tri Widya; Poerana, Ana Fitriana; Husein, Shahreen (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Karawang stands as the third district most at risk from flooding. The Kamojing Dam, serving as a reservoir and regulator of water flow in the Cikampek area of Karawang Regency, plays a crucial role in controlling flood disasters. Currently over a century old, the Kamojing Dam is susceptible to disasters such as dam failures and ruptures, which can lead to sudden flooding. Therefore, disaster mitigation efforts are needed in an effort to minimize the risk due to disasters, one of which is through risk communication. This study aimed to investigate the role of risk communication in mitigating the disaster caused by the Kamojing Dam failure. This study employs a qualitative research method, utilizing in-depth interviews. The study's results show that Kamojing Dam uses both internal and external communication systems to communicate dam conditions through the WhatsApp Group, thereby minimizing disaster risks. External risk communication involves various stakeholders who act as liaisons between dam managers and the community. Additionally, the dam implements an early warning system through various media.